THE EFFECT OF THE DISCOVERY LEARNING MODEL ASSISTED BY ELKPD ON THE ABILITY TO UNDERSTAND MATHEMATICAL CONCEPTS OF JUNIOR HIGH SCHOOL STUDENTS - Anshori, Muhamad Irfan; Yensy, Nurul Astuty; Stiadi, Elwan (Universitas Tanjungpura, 2025)
This study aims to analyze the effect of the Discovery Learning model assisted by ELKPD on the ability to understand mathematical concepts of junior high school students. This study uses three-dimensional shapes with flat sides. The method used in this study was quantitative research with a Quasi Experiment design. The sampling technique used purposive sampling. The data collection technique was carried out by conducting a description test to measure the ability to understand mathematical concepts. The Discovery Learning model assisted by ELKPD was applied to class VIII.3 as the experimental class, while class VIII.1, as the control class, only applied the Discovery Learning model without using ELKPD. The ELKPD used in this study is based on the EdForm website. EdForm is a teaching material used to attract student